2-(3-Methyl-1-phenyl-1H-pyrazol-4-yl)-3-phenylthiazolidin-4-ones as Potent Antioxidant and Antidiabetic Agent - Sen, Sandip; De, Biplab; Easwari, T.S. (Asian Journal of Chemistry, 2014)
A series of 2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)-3-phenylthiazolidin-4-ones (7a-7j) were synthesized by intramolecular cyclization of imines (6a-6j) with thioglycolic acid in the presence of acid catalyst. The Schiff bases were obtained upon reaction between electrophilic carbon atom of 3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde (4) and nucleophilic nitrogen atom of substituted aromatic amines. in vitro Antioxidant activity was determined by DPPH redical scavenging assay mehod using ascorbic acid as standard. The antidiabetic activity was carried out by streptazocine induced diabetic method using rosiglitazone as standard drug on wister rats. From the study it were found that 3-(4-chlorophenyl)-2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)thiazolidin-4-one (7a), 3-(4-bromophenyl)-2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)thiazolidin-4-one (7b), 3-(3,4-dichlorophenyl)-2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)thiazolidin-4-one (7d), 3-(3,4-difluorophenyl)-2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)thiazolidin-4-one (7f) 2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)-3-(4-(trifluoromethyl)phenyl)thiazolidin-4-one (7h), 3-(4-methoxyphenyl)-2-(3-methyl-1-phenyl-1H-pyrazol-4-yl)thiazolidin-4-one (7j) shown more IC50 compare to standard. Where as compound 7a, 7b, 7h, 7j show more significant antidiabetic effect against hyperglycemic rats compare to standard drugs at the dose of 5 mg/kg after 21 days of treatment.